DINCOLO ȘI DINCOACE DE TEORIA ȘI PRACTICA INFORMĂRII ȘI DOCUMENTĂRII: (O hermeneutică necesară și un cadru posibil) - KIRALY, editor „Philobiblon”, BCU „Lucian Blaga”, Cluj-Napoca, Istvan (BIBLIOPOLIS, 2020)
The author highlights the problem of existing and dominant mentalities in our profession that could be changed. Without getting into complicated conceptualization, we can say that library publications par excellence belongs to the public sphere. They should problematize mentality, situation, status, image orientation, social recognition and status of the profession and our institutions. It is very interesting to analyse the frequency of reflection and analysis on these issues published on the pages of Roumanian library magazines. It is interesting to study the proportion of debates and explicit confrontations, arguments and polemical ideas, opinions and projects … presented in this professional publications. Further the author talk about the journal recently published by the Central University Library from Cluj Napoca, Romania – Philobiblon. The concept of the journal Philobiblon is defined by the logo Ideas-Books-Society-Readings. The journal Philobiblon contains permanent sections: Studies, Articles, Miscelanea. Philobiblon is an open and dynamic forum for researches.